Maturity patterns and harvest indices for 'Gala', 'Golden Delicious' and 'Fuji' apples - Argenta, Luiz Carlos; Bender, Renar João; Kreuz, Carlos Leonor; Monardo, Marcia (Pesquisa Agropecuaria Brasileira, 1995)
The maturity patterns 'Gala', 'Golden Delicious' and 'Fuji' apples and the relationship to commercial harvest time were evaluated in Santa Catarina State, South Brazil, during 1985 to 1994. During the maturation period, linear and quadratic tendencies in the starch index and in the total soluble solids increase, as well as in the firmness and acidity reduction were observed. The changes of physicochemical parameters started before the commercial picking period, indicating that they can be used as practical indices for predieting the harvest time. Starch indices between 3 and 5 for 'Gala' and 'Golden Delicious' and between 4 to 6 for 'Fuji' apples were associated with the commercial harvest dates. At this period the largest acidity, TSS and firmness indices occurred in 'Golden Delicious', 'Fuji' and 'Gala' apples, respectively. The seasonal variations for all parameters were largest for 'Gala' and lowest to 'Fuji' apples. In some cases, seasonal variations were larger than harvest dates effects. Apparently, the use of index Streif obtained by using firmness, TSS and starch indices is a reliable method to define the correct picking dates.
Keywords: maturity index; Malus domestica; postharvest